O projeto Viva e Reviva Goiás e suas contribuições para a educação patrimonial em Goiás (1999 – 2010) - Queiroz, Cassia Maria de (2021)
This research aims to analyze the Heritage Education project Viva e Reviva Goiás from documentation related to educational activities develop between 1999 and 2007 by public and private schools from Cidade de Goiás. Conceived in 1999, the project was officially launched in 2000 by the Education Office of the State of Goiás. This Project of Heritage Education was chosen as an object of study due to its pioneering character in Goiás and for being a pilot project whose experience originated the Programa Viva e Reviva which was carried out by some cities in the state. The documental corpus being studied is composed by a final report with subprojects proposed by schools in Cidade de Goiás, some official letters, folders, handwritten documents, questionnaires, among others. In addition to document analysis oral history was used by means of interviews with teachers who integrated the Programa Viva e Reviva. As the Projeto Viva e Reviva was being carried out, the community was involved in the activities proposed by the schools enabling a series of developments in the educational practices seeking to identify and protect the local cultural heritage: places, buildings, knowledge, festivals and artistic expressions from different groups from the vilaboense community. Thus, this study aims to identify the goals and the conception of the Heritage Education present in this project to discuss the bases that guided the actions developed in the survey of the material and immaterial heritage of Cidade de Goiás. The final product proposed is a documentary concerning Projeto Viva e Reviva Goiás created from the research and experience of the program team, seeking to inspire students, teachers and communities to create their own video to record their cultural heritage.